2022
DOI: 10.3390/jcm11113243
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Choroidal Morphology and Vasculature in the Phenotype of Pachychoroid Diseases by Swept-Source OCT and OCTA

Abstract: The objective of this study was to characterize the choroidal morphology and vasculature in pachychoroid diseases (PCD). A total of 49 eyes with polypoidal choroidal vasculopathy (PCV), 43 eyes with neovascular age-related macular degeneration (nAMD), and 50 eyes with central serous chorioretinopathy (CSC), along with 80 healthy eyes, were enrolled in this nested case-control study. The swept-source optical coherent tomography (OCT), OCT angiography, and En face images were quantitatively analyzed. Multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…On the other hand, there was no significant difference in CVD between the two groups in our study. A recent study suggested that decreased vascular density in the superficial choroid is an independent risk factor for polyp development [ 31 ]. Thinning of the superficial layer may be responsible for the reduced vascular density.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there was no significant difference in CVD between the two groups in our study. A recent study suggested that decreased vascular density in the superficial choroid is an independent risk factor for polyp development [ 31 ]. Thinning of the superficial layer may be responsible for the reduced vascular density.…”
Section: Discussionmentioning
confidence: 99%
“…If the disease progresses, the terminal blood vessels bulge locally and manifest as polypoid lesions (12,14). Qiu et al (15) found statistically significant differences in the proportion of diffuse collateral circulation between PCV, neovascular AMD, central serous chorioretinopathy (CSC) and healthy controls. During the progression of pachychoroid spectrum disease, hyperaemia of the vortex veins may gradually improve with the development of anastomosis between the superior and inferior vortex veins (16).…”
Section: Discussionmentioning
confidence: 99%
“…Substandard scans in which the signal strength (SS) fell below the manufacturer's recommended cut-off point (SS < 7) and images with significant eye movement were excluded. Choriocapillaris density (CCD) was measured by OCTA, and Sattler + Haller vessel density was quantified by en face images to avoid sensitivity roll-off with increasing imaging depth [ 10 , 11 ]. To avoid the shadowing effect of neurosensory detachment that affects the OCTA flow signal in the choriocapillaris, we applied the CCD of a fellow eye for analysis [ 12 ].…”
Section: Methodsmentioning
confidence: 99%